Biology of Amblypharyngodon mola (Hamilton) from a floodplain wetland, West Bengal - Suresh, V R; Biswas, B K; Vinci, G K; Mitra, K; Mukherjee, A (Indian Journal of Fisheries, 2011)
Biology of Amblypharyngodon mola from a floodplain wetland was studied during May 2003 to April 2004. The length-weight relationship of the fish suggested isometric growth. The regression models obtained was log W = 2.9819 X - 4.9826 log L, R2 = 0.7278 for male and log W = 3.0579 X -5.0873 log L, R2 = 0.9213 for female. The fish is a herbivore, feeding mainly on species belonging to the orders Myxophyceae, Bacillariophyceae, Chlorophyceae and Euglenophyceae. November-February was the most active feeding period. The sex ratio was 1:7.7. The fecundity ranged from 21 to 16867, while the relative fecundity ranged from 7 to 2122. The length at first maturity was 51-56 mm for males and 39-44 mm for females. The ova diameter ranged from 0.05 to 0.7 mm. The fish breed once for a definite period during April-October in the wetland.